2J(29Si-O-29Si) coupling constants in oligosiloxanes - Kurfürst, Milan; Schraml, Jan (Magnetic resonance in chemistry, 2007)
The absolute values of spin-spin couplings between (29)Si nuclei in siloxanes, (2)J((29)Si-O-(29)Si), were determined. The couplings are small and cover a narrow range of values (0-5 Hz). The coupling constants depend on the branching or on the number of electronegative substituents on the Si-O-Si moiety.